Perekonomian 2 Sektor: Perekonomian Rumah Tangga Dan Perusahaan - Adil Pratomo; Fadhul Rohman; Renita Dewi; Zulfa Dela Octavia (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The modern economy, with the household and corporate sectors as the main players, is involved in a complex structure. This research uses a qualitative approach to explore the interaction between the two in a dynamic economic context. Qualitative analysis reveals how the two interact in a changing environment. Researchers highlight the importance of verifying household income for purposes such as loans and evaluating financial condition, which involves examining documents such as pay slips and tax reports. Financial challenges include effective management of income and expenses, as well as developing long-term financial plans. Changes in the economic situation and rising prices of goods can pose other challenges in business management. The company faces ever-changing competition by implementing product diversification strategies, increasing operational efficiency, and developing new markets. They also focus on managing risk, maintaining healthy finances, and adapting to changing regulations and market conditions. This research highlights the linkages between the household and corporate sectors and their implications for overall economic stability. With a deeper understanding of the dynamics in these two sectors, this article provides insights for policy makers, business people and the general public in formulating more effective strategies to increase prosperity and economic growth.